2014
DOI: 10.1038/srep05705
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient targeted mutagenesis in one-cell mouse embryos mediated by the TALEN and CRISPR/Cas systems

Abstract: Since the establishment of embryonic stem (ES) cell lines, the combined use of gene targeting with homologous recombination has aided in elucidating the functions of various genes. However, the ES cell technique is inefficient and time-consuming. Recently, two new gene-targeting technologies have been developed: the transcription activator-like effector nuclease (TALEN) system, and the clustered regularly interspaced short palindromic repeat (CRISPR)/CRISPR-associated protein (Cas) system. In addition to aidin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 44 publications
1
56
0
Order By: Relevance
“…In mammalian cells, however, MMEJ was observed in the presence of normal NHEJ function when using truncation mutants of the V(D)J recombination proteins Rag1 and Rag2 during recombination [54,55]. Several recent studies suggested that MMEJ may be utilized to repair TALENor CRISPR/Cas9-induced DSBs in different animal models [56,57]. While this manuscript was under review, it was reported that precise in-frame knock-in could be achieved in zebrafish by using short homologous sequences (10-40 bp) [58], although it is unknown whether MMEJ, SSA or both were involved in that process.…”
Section: Discussionmentioning
confidence: 99%
“…In mammalian cells, however, MMEJ was observed in the presence of normal NHEJ function when using truncation mutants of the V(D)J recombination proteins Rag1 and Rag2 during recombination [54,55]. Several recent studies suggested that MMEJ may be utilized to repair TALENor CRISPR/Cas9-induced DSBs in different animal models [56,57]. While this manuscript was under review, it was reported that precise in-frame knock-in could be achieved in zebrafish by using short homologous sequences (10-40 bp) [58], although it is unknown whether MMEJ, SSA or both were involved in that process.…”
Section: Discussionmentioning
confidence: 99%
“…Since each cell has a choice of whether to repair a break through NHEJ or HDR, a variety of different repair events will be present in the injected organism (and in individual cells). The frequency at which both alleles of a gene are affected has been reported to be high enough to visualize null phenotypes in developing mice and zebrafish (Jao et al 2013;Wang et al 2013a;Yasue et al 2014;Yen et al 2014). For example, zebrafish and mice injected with a gRNA targeting the tyrosinase gene resulted in embryos displaying mosaic pigmentation (Jao et al 2013;Yen et al 2014).…”
Section: Practical Considerations Of Using Rgns In Developing Organismsmentioning
confidence: 99%
“…As described earlier in this review, MMEJ has been utilized for the efficient gene knockout. The availability of MMEJ in genome editing applications has also been proven by various studies reporting the frequent observation of the traces of MMEJ repair on the edited alleles (Yasue et al 2014;Li et al 2015). The first example of MMEJ-dependent integration of donor plasmid was reported in 2014, where microhomologous ends between the genomic target site and exogenous DNA fragment were generated by simultaneous cleavage of genomic DNA and the donor vector (Nakade et al 2014).…”
Section: Mmej/ssa-mediated Gene Knock-inmentioning
confidence: 99%